Pandinus imperator scorpion venom blocks voltage-gated potassium channels in nerve fibers - Pappone, PA (J Neurosci, 1987)
We have examined the effects of venom from the scorpion Pandinus imperator on the membrane currents of voltage-clamped frog myelinated nerve fibers using the Vaseline-gap method. Crude venom, applied externally in concentrations from 50 to 500 micrograms/ml, selectively blocked the voltage-gated potassium currents without affecting nodal sodium currents or resting conductances. Block of potassium channels by Pandinus venom was highly dependent on the membrane voltage, being greater at negative potentials than at positive potentials. The blocking effects of Pandinus venom were irreversible on the time scale of our experiments; however, even high concentrations of venom failed to block potassium currents completely at positive potentials. These results suggest that Pandinus venom contains a component(s) that interacts specifically and strongly with a subpopulation of axonal potassium channels.